Adenovirus‐associated antibodies in UK cohort of hemophilia patients: A seroprevalence study of the presence of adenovirus‐associated virus vector–serotypes AAV5 and AAV8 neutralizing activity and antibodies in patients with hemophilia A. Issue 2 (25th January 2019) - Stanford, Sophia; Pink, Ruth; Creagh, Desmond; Clark, Amanda; Lowe, Gillian; Curry, Nicola; Pasi, John; Perry, David; Fong, Sylvia; Hayes, Gregory; Chandrakumaran, Kandiah; Rangarajan, Savita
Abstract: Background: Current treatment for severe hemophilia A is replacement of deficient factor. Although replacement therapy has improved life expectancy and quality, limitations include frequent infusions and high costs. Gene therapy is a potential alternative that utilizes an adeno‐associated virus (AAV) vector containing the human genetic code for factor 8 (FVIII) that transduces the liver, enabling endogenous production of FVIII. Individuals with preexisting immunity to AAV serotypes may be less likely to benefit from this treatment. Objectives: This study measured seroprevalence of antibodies to AAV5 and 8 in an UK adult hemophilia A cohort. Patients/Methods: Patients were recruited from seven hemophilia centres in the UK. Citrated plasma samples from 100 patients were tested for preexisting activities against AAV5 and 8 using AAV transduction inhibition and total antibodies assays. Results: Twent‐one percent of patients had antibodies against AAV5 and 23% had antibodies against AAV8. Twenty‐five percent and 38% of patients exhibited inhibitors of AAV5 or AAV8 cellular transduction respectively. Overall seroprevalence using either assay against AAV5 was 30% and against AAV8 was 40% in this cohort of hemophilia A patients. Seropositivity for both AAV5 and AAV8 was seen in 24% of participants. Conclusions: Screening for preexisting immunity may be important in identifying patients most likely to benefit from gene therapy. Clinical studies may be needed to evaluate the impact of preexisting immunity on the safety and efficacy of AAV mediated gene therapy.